Analysis of Emergence of Quinolone-Resistant Gonococci in Greece by Combined Use of Neisseria gonorrhoeae Multiantigen Sequence Typing and Multilocus Sequence Typing - Mavroidi, Angeliki (American Society for Microbiology, 2011)
The prevalence of quinolone-resistant Neisseria gonorrhoeae (QRNG) in Greece remained low from 1997 to 2003 but increased dramatically from 11% to 56% between 2004 and 2007. N. gonorrhoeae multiantigen sequence typing (NG-MAST) and multilocus sequence typing (MLST) were used to investigate trends in quinolone resistance from 1997 to 2007 and explore the origins of the recent increase in QRNG. We characterized 295 QRNG isolates from the study period and 233 quinolone-susceptible (QS) gonococci from 2004 and 2005, when the rapid increase in QRNG occurred. From 1997 to 1999, an outbreak of QRNG was due to the dissemination of isolates of serovar Arst that belonged to two closely related genotypes. Few QRNG isolates, of diverse genotypes, were present between 2001 and 2003, whereas the sharp increase in QRNG from 2004 onwards was due to the appearance of serovar Bropyst isolates of several major NG-MAST sequence type (STs) that previously had not been identified in Greece. These isolates were shown by MLST to be variants of a single multiply antibiotic-resistant QRNG strain (ST1901) that appeared in Greece and rapidly diversified into 31 NG-MAST STs. There were no isolates of MLST ST1901 or any of the 31 NG-MAST STs among QS isolates from 2004 and 2005 or among 8 representatives of multiresistant but quinolone-susceptible serovar Bropyst isolates circulating in Greece during the 1990s, supporting the view that the recent increase in QRNG was due to importation of a QRNG strain(s) of MLST ST1901 into Greece. Recently, multiresistant QRNG isolates of ST1901 with reduced susceptibility to the newer cephalosporins have appeared in Greece.